Assessing elements of a family approach to reduce adolescent drinking frequency: parent–adolescent relationship, knowledge management and keeping secrets - McCann, Mark (Addiction, 2016)
AIMS: To estimate (1) the associations between parent–adolescent relationship, parental knowledge and subsequent adolescent drinking frequency and (2) the influence of alcohol use on parental knowledge. DESIGN: Path analysis of school based cohort study with annual surveys. SETTING: Post‐primary schools from urban and intermediate/rural areas in Northern Ireland. PARTICIPANTS: A total of 4937 post‐primary school students aged approximately 11 years in 2000 followed until approximately age 16 years in 2005. MEASUREMENTS: Pupil‐reported measures of: frequency of alcohol use; parent–child relationship quality; subdimensions of parental monitoring: parental control, parental solicitation, child disclosure and child secrecy. FINDINGS: Higher levels of parental control [ordinal logistic odds ratio (OR) = 0.86, 95% confidence interval (CI) = 0.78, 0.95] and lower levels of child secrecy (OR = 0.83, 95% CI = 0.75, 0.92) were associated subsequently with less frequent alcohol use. Parental solicitation and parent–child relationship quality were not associated with drinking frequency. Weekly alcohol drinking was associated with higher subsequent secrecy (beta −0.42, 95% CI = –0.53, −0.32) and lower parental control (beta −0.15, 95% CI = –0.26, −0.04). Secrecy was more strongly predictive of alcohol use at younger compared with older ages (P = 0.02), and alcohol use was associated less strongly with parental control among families with poorer relationships (P = 0.04). CONCLUSIONS: Adolescent alcohol use appears to increase as parental control decreases and child secrecy increases. Greater parental control is associated with less frequent adolescent drinking subsequently, while parent–child attachment and parental solicitation have little influence on alcohol use.